Crossing the quality chasm : a new health system for the 21st century (Quality chasm series., 2001)
Report concludes that the nation's health care industry has failed to provide safe, quality care consistently to all Americans, and recommends overhaul, suggesting that Congress allocate funds to improve patient records and care for 15 common chronic health conditions over a five-year period.